IMPLIKASI PENERAPAN BALANCE SCORECARD DAN KEPUASAN PELANGGAN TERHADAP KINERJA PENJUALAN DI PT MAHKOTA INTI SEJAHTERA. - Gazali . (Journal Of Communication Education, 2016)
ABSTRACTThis study aims to identify the implications of the Balanced Scorecard and Customer Satisfaction implementations to the selling performance of Suzuki motorcycles at PT. Mahkota Inti Sejahtera, Jakarta. Research sample involves 147 respondents, who are customers of Suzuki, and determined by sampling saturation technique; Furthermore the data’s gained through the questionnaire. Correlational research methodology uses a model that studies the connection or influence of variables through double linear regression. The degree level of connection is represented in the correlation coefficient and used to test the hypothesis. The results prove that the application of Balanced Scorecard partially governs towards the selling performance. While the customer satisfaction also have a significant affect towards the selling performance. The Balance Scorecard and customer satisfaction variables effect simultaneously on the selling performance of Suzuki motorcycles at PT. Mahkota Inti Sejahtera. Keywords: Balance Scorecard, Customer Satisfaction, Sales Performance